Restrukturisasi Berpikir Siswa Melalui Pemunculan Skema dalam Menyelesaikan Soal Ujian Nasional Mata Pelajaran Matematika - Siti Aisya; Kusaeri Kusaeri; Sutini Sutini (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2019)
Defragmentation of student’s thinking structures through scheme appearance to fix pseudo thinking student’s in solving problems HOTS test type for mathematics in the National Exam 2018. Pseudo Thinking happened because students did not reflect before answering, so students give the wrong answer. Pseudo thinking divided into false-pseudo thinking and true-pseudo-thinking. Hence, in this research to describe student’s structural thinking errors and the process of defragmentation of student’s thinking structures through scheme appearance to fix student’s pseudo thinking in solving problems of HOTS test type for mathematics in the National Exam 2018. This research is qualitative research with descriptive type. Researchers used three subjects to describe the defragmentation process of scheme appearance. The result of this research, all subjects experienced false-pseudo thinking and true-pseudo thinking. From the research, subjects can reveals that the process of scheme appearance that has been previously. So subjects can solve problems.